Innovative integration of sustainable urban development for bungalow homes in Meru, Ipoh - Nurul Hisham, Muhammad Azan; Azahar, Muhammad Mifzal Haziq; Zaide, Nurul Hawa; Mohamad, Junainah (2024)
Vista Heaven, a high-end luxury project consisting of 22 bungalows located in Meru, Ipoh, is raising the bar for sustainable living. This project meets the need for high-end residences by incorporating energy-saving elements like smart plugs, LED lights, cool roof materials, solar panels, and rainwater collection systems. These technologies play a role in creating an EcoSmart Sanctuary, highlighting energy efficiency, water conservation, and sustainability as key components. Although facing obstacles such as expensive initial investments, upkeep, and changing user behaviours, Vista Heaven provides important lessons for policymakers, developers, and consumers. It emphasises the possibility of combining luxury living with eco-friendly practices, showcasing the need for ongoing research, policy backing, and education to encourage sustainability in housing areas. Vista Heaven serves as a template for tackling climate change by promoting projects that prioritise both human well-being and environmental health, demonstrating that sustainable living is feasible and attractive.